LARGE-SCALE EXPANSION OF HYPOXIA AT MARINE BENTHAL ZONE IN GEOMORPHOLOGICALLY COMPARABLE BAYS-FJORDS OF CRIMEA PENINSULA UNDER DIFFERENT TECHNOGENIC LOADS - Maksim B. Gulin; Igor V. Masberg; Ekaterina А. Ivanova (Юг России: экология, развитие)
Aim. Comparative analysis of the aeration features of the bottom waters during the different seasons of the year between the Sevastopol and Donuzlav Bays as geomorphological similar in configuration semi-closed sea reservoirs of the Black Sea under different anthropogenic loads. Material and methods. Sevastopol and Donuzlav Bays, located in the Western part of the Crimean Peninsula, were studied. The concentration and total consumption of dissolved oxygen in the water column and the bottom layer were determined in situ using a digital LDO analyzer. The redox potential in bottom sediments was measured using a platinum electrode. Results. Aeration of the water column in the Sevastopol seaside is suitable for normal life of pelagic and epibenthic organisms. At the same time, in the Sevastopol and Donuzlav Bays the large-scale anoxia in the surface layer of bottom sediments was found. Also, the muddy sediments of the Sevastopol Bay’ bed can be an oxygen-deficient extreme biotope for most of the year, the minimum concentration of O2 in the bottom water is not higher than 0.11-0.36 mg/l. The benthal zone here was well aerated only at the end of November. Conclusion. The general patterns of benthic hypoxia were identified for such coast objects as Sevastopol and the Donuzlav Bays, which are similar by their contours and recent seabed structures. Benthal zones of both investigated bays-fjords can be attributed to hypoxic high-gradient habitats, that have a whole generality with oxygen-deficient marine waters habitats – estuarine zones, areas of gas seeps, etc. Strong oxygen deficiency, toxic H2S contamination coupled with organic enrichment a typically benthic environment for such biotopes.